A de-civilizing reversal or system normal?: rising lethal violence in post-recession austerity United Kingdom - Ellis, Anthony (The British journal of criminology, 2019)
This article offers incipient theoretical analysis and reflections on the recent rises in lethal violence recorded in the United Kingdom. The rises have attracted considerable media attention, with the more informed discussions drawing plausible causal associations between rising lethal violence and the policy context of austerity. Criminology, however, has been relatively silent so far on the recent rises and this potential association. In response, this article attempts to stimulate debate by critically considering the utility of one of the most widely cited theoretical frameworks in the study of historical patterns of violence in the western nations: the ‘civilizing process’. The article then moves on to consider the applicability of insights from the incipient ultra-realist criminological perspective. The article suggests that the ultra-realist concept of the ‘pseudo-pacification process’ provides a useful means of furthering our understanding of these rises in the current socioeconomic context of post-crash capitalism.